A quality center (Journal of Parents and Teachers, 2023)
The selection of schools is a crucial moment for the families. Therefore, they search what it’s usually called as “quality school”. In the article some points to avoid and follow are exposed, where the evaluation gets a lot of importance.
Keywords: quality; key points; education; evaluation